Population genetics of the Federally Threatened Miccosukee gooseberry (Ribes echinellum), an endemic North American species - Oleas, Nora (2014)
Ribes echinellum (Coville) Rehder (Miccosukee gooseberry; Grossulariaceae) is a Federally Threatened species known from only two localities: Jefferson County (Florida, FL) and McCormick County (South Carolina, SC). This perennial shrub, ca. 1 m tall, is deciduous, and reproduces both vegetatively (clonal growth) and sexually (seed production). Recent surveys of the FL population revealed a dramatic decline in plant numbers. To assist in conservation and management of this species in FL and SC populations, microsatellite genetic markers were used to identify genotypes and assess the genetic structure of R. echinellum. We genotyped seven microsatellite loci in 102 individuals: 74 collected in FL and 28 in SC. Unbiased heterozygosity was between 0.28 and 0.53. All seven loci were polymorphic, showing a range of 1.52-2.13 effective number of alleles per locus (mean = 1.75). The two populations of R. echinellum show low genetic diversity, especially in SC. Clonality was not widespread, but was higher in the SC population. Both populations show signatures of bottlenecks but isolation by distance was not evident. We found significant deviation from HW equilibrium, with higher number of heterozygotes than expected. However when HW test was done for the combined populations as two separate groups, only FL showed a significant HW test and for SC the test was non-significant. Bayesian analysis and FST values suggest high genetic divergence between the populations. These results are important for developing a recovery plan and an ex situ and reintroduction conservation programs. © 2014 Springer Science+Business Media Dordrecht (outside the USA).